In search of contemporary garden typologies in Moroccan and Syrian courtyard gardens - Abdul Latiff, Zainab; Mohd. Yaman, Maheran (American Scientific Publishers, 2017)
The courtyard garden represents a constant feature of domestic architecture in most Muslim regions; however, it was developed in different ways as influenced by many local factors. Its organization, configuration and social role, suggest more a sociocultural need than a physical one. Therefore, it is important to base them on this ground rather than the climatic argument. The method of content analysis and library search has been adopted in this study. To conclude, to ensure the existence of courtyard gardens, it is important to think courtyards as a social space able to adapt to the changing conditions of modern life, anywhere in the world to ensure a continuous link between history and the present day.